Whether mindfulness-guided therapy can be a new direction for the rehabilitation of patients with Parkinson’s disease: a network meta-analysis of non-pharmacological alternative motor-/sensory-based interventions - He, Shenglan; Fang, Wanyi; Wu, Jiaoyang; Lv, Hang; Zhang, Jueyu; Wang, Tunyi; Huang, Yingjie; Li, Guangyao; Li, Min (Frontiers in Psychology, 2023)
Background The treatment for Parkinson’s disease (PD) consumes a lot of manpower and financial resources. Non-pharmacological alternative motor-/sensory-based interventions are optimized for the rehabilitation of PD patients. Mindfulness-based therapy shows ideal efficacy, but the diversity of the therapy brings difficulties to the selection of clinicians and patients. Methods Network meta-analysis in the Bayesian framework was used to evaluate the efficacy of non-pharmacological alternative motor-/sensory-based interventions in improving motor and non-motor symptoms in PD patients. Results A total of 58 studies (2,227 patients) were included. Compared with the non-intervention group, qigong was associated with improved outcomes in the Timed Up and Go (TUG) test (mean difference (MD) −5.54, 95% confidence interval (CI) −8.28 to −2.77), and UPDRS-I (MD −15.50, 95% CI −19.93 to −7.63). Differences between non-pharmacological alternative motor-/sensory-based interventions were not significant for PDQ-39, UPDRS-I, or UPDRS-II; however, qigong was superior to dance (MD −3.91, 95% CI −6.90 to −0.95), Tai Chi (MD −3.54, 95% CI −6.53 to −0.69), acupuncture (MD −6.75, 95% CI −10.86 to −2.70), music (MD -3.91, 95% CI −7.49 to −0.48), and exercise (MD −3.91, 95% CI −6.49 to −1.33) in the TUG test. Conclusion This network meta-analysis supports mindfulness-based therapy (e.g., qigong, yoga, and Tai Chi) as a preferred non-pharmacological alternative motor-/sensory-based intervention for PD rehabilitation. Systematic review registration https://inplasy.com/inplasy-2022-10-0109/, INPLASY2022100109.